First principles of smart manufacturing. Issue 4 (23rd May 2022) - Leiva, Conrad
Abstract: The democratizing of innovation and technology happens when tools and expertise are made affordable and accessible at scale to most manufacturers. To realize the democratization of smart manufacturing innovation, it is not only necessary to democratize the technology, but also necessary to provide wide access to the knowledge required to implement the strategies and leverage the solutions and insights in a more digitally enabled manufacturing ecosystem. We are at a point in the journey where it is time to converge on a concrete set of guiding principles and a framework that organizes expectations and requirements for the implementation of smart manufacturing. This paper summarizes the practices that define smart manufacturing as developed by the industry leaders, early adopters, and expert practitioners working in the ecosystem at CESMII, the smart manufacturing institute. In smart manufacturing, organizations, people, and technology work in synergy via processes and technology‐based solutions that follow these seven First Principles: Flat & real‐time, open & interoperable, proactive & semi‐autonomous, sustainable & energy efficient, secure, scalable, orchestrated & resilient. All the design principles must be considered to fully realize the vision for smart manufacturing. This paper will further explain how the seven principles work collectively to achieve new levels of connectivity, intelligence, and automation in the manufacturing ecosystem.